Effects of vaccinating beef dams precalving and calves preweaning with a Pasteurella haemolytica vaccine - Wankel, L.E.; Marston, T.T.; Stokka, Gerald L.; Brethour, J.R.; Rozell, Timothy G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our objective was to determine if vaccinating dams precalving and calves preweaning for Pasteurella haemolytica could effect serum antibody titers in dams, and the pre- and post-weaning health and performance of their calves. Vaccination increased serum antibody titers in multiparous cows, but not first-calf heifers. Precalving vaccination had minimal effects on mortality and morbidity of calves before or after weaning. Subsequent steer feedlot gains were unaffected by precalving and preweaning vaccinations and carcasses were not affected. However, heifers’ weight gains were greater from weaning to one year of age when reared by vaccinated dams.
Keywords: Beef; Passive immunity; Vaccination; Antibody